Efektivitas Media Video Animasi dalam Kemampuan Menulis Teks Biografi pada Siswa Kelas X SMK Negeri 1 Cikarang Pusat - Tiara Putri Erhani; Sutri; Cut Nuraini (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2026)
This study aims to determine the effectiveness of using animated video media in the ability to write biographical texts for class X students of SMK Negeri 1 Cikarang Pusat. This study was motivated by the low ability of students in writing biographical texts caused by the use of learning media that is less varied and still teacher-centered. The research method used is a quantitative approach with a quasi experimental design using a pretest and posttest model with a control group. The research subjects consisted of two classes, namely class X TEI 2 as the experimental class given treatment in the form of animated video media and class X TEI 3 as the control class using conventional learning. Data collection techniques were carried out through biographical text writing tests, observations, questionnaires, and documentation. The research instruments were in the form of pretest and posttest questions that had been tested for validity and reliability. Data were analyzed using normality tests, homogeneity tests, and hypothesis tests (t-tests) with the help of the SPSS 25 program. The results showed that there was a significant difference between the ability to write biographical texts of students who used animated video media and students who did not use the media. The average posttest score of the experimental class was higher than that of the control class. Thus, it can be concluded that the use of animated video media is effective in improving the writing skills of biographical texts in grade 10 students at SMK Negeri 1 Cikarang Pusat.